If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(x + 1) + -1log(3) = -1log(x + 1) Reorder the terms: glo(1 + x) + -1log(3) = -1log(x + 1) (1 * glo + x * glo) + -1log(3) = -1log(x + 1) (1glo + glox) + -1log(3) = -1log(x + 1) Reorder the terms for easier multiplication: 1glo + glox + -1 * 3glo = -1log(x + 1) Multiply -1 * 3 1glo + glox + -3glo = -1log(x + 1) Reorder the terms: 1glo + -3glo + glox = -1log(x + 1) Combine like terms: 1glo + -3glo = -2glo -2glo + glox = -1log(x + 1) Reorder the terms: -2glo + glox = -1glo(1 + x) -2glo + glox = (1 * -1glo + x * -1glo) -2glo + glox = (-1glo + -1glox) Solving -2glo + glox = -1glo + -1glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'glo' to each side of the equation. -2glo + glo + glox = -1glo + glo + -1glox Combine like terms: -2glo + glo = -1glo -1glo + glox = -1glo + glo + -1glox Combine like terms: -1glo + glo = 0 -1glo + glox = 0 + -1glox -1glo + glox = -1glox Add 'glox' to each side of the equation. -1glo + glox + glox = -1glox + glox Combine like terms: glox + glox = 2glox -1glo + 2glox = -1glox + glox Combine like terms: -1glox + glox = 0 -1glo + 2glox = 0 Factor out the Greatest Common Factor (GCF), 'glo'. glo(-1 + 2x) = 0Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1 + 2x)' equal to zero and attempt to solve: Simplifying -1 + 2x = 0 Solving -1 + 2x = 0 Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 0 + 1 2x = 0 + 1 Combine like terms: 0 + 1 = 1 2x = 1 Add '-2x' to each side of the equation. 2x + -2x = 1 + -2x Combine like terms: 2x + -2x = 0 0 = 1 + -2x Simplifying 0 = 1 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| m-4/5 | | 5y^2-2=9y | | 15-12n=n+12 | | log^3(12x+3)=5 | | 9=-9+17 | | 159=14x+19 | | f(x)=2x^5-14x^3-10x^2-4250find(5) | | x+2x=-36 | | 7x+(-2)=44 | | x/3-x/2=4 | | 9x=6318 | | x+(x+4)+(x+7)+(x+9)+(x+10)=60 | | 0.5(x-4)=80 | | (3b^2+2b-4)/(b-2) | | -7k/8=49 | | -7(2x+6)=70 | | 7x6+2x10/2 | | 7a-4a= | | 15+9x=6x+8x-20 | | 9-1+5= | | f=n/4+37 | | 10+4(3p+10)=16 | | 5a/6+2b/9 | | 3x^2-10x-17=0 | | (5b+4)-2(b-5)=7 | | 5x/6-x/3 | | 2x-16=-8 | | 21(5+-4)=43 | | 21(5+-4)=7 | | z^2+8z+16= | | b+2.35=9.78+2b+722 | | .3a-3.25=5.75 |